A suggested unit on meal-planning and serving based on family customs - Bean, Helen J., author; Morgan, David H., advisor; Williamson, Maude, committee member; Rice, Juanita, committee member; Kinyon, Kate Pamela Woodard, 1881-, committee member; Kezer, Alvin, 1877-, committee member (Colorado State University. Libraries, 1940)
To view the abstract, please see the full text of the document.
Keywords: Home economics -- Study and teaching